Make change happen : get to grips with managing change in business - Coyne, Ian (Pearson, 2014)
The definitive guide to change management in business. Change in business is constant. Manage it well and you'll grow your business, stay ahead of the curve and take full advantage of every new opportunity. The key to successful, well-managed change is in this book. Written by a specialist, its practical, visual, step-by-step approach will make sure you're always on the right track, that change in your business is smooth, stress free and well-structured, and that all your stakeholders remain on board every step of the way. Make Change Happen gives you the start-to-finish plan you need t.